If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 4 + M = -4 Reorder the terms: 4 + M + 3m = -4 Solving 4 + M + 3m = -4 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + M + -4 + 3m = -4 + -4 Reorder the terms: 4 + -4 + M + 3m = -4 + -4 Combine like terms: 4 + -4 = 0 0 + M + 3m = -4 + -4 M + 3m = -4 + -4 Combine like terms: -4 + -4 = -8 M + 3m = -8 Add '-3m' to each side of the equation. M + 3m + -3m = -8 + -3m Combine like terms: 3m + -3m = 0 M + 0 = -8 + -3m M = -8 + -3m Simplifying M = -8 + -3m
| 3(x-2)=5x+50 | | z^4-2zi=0 | | 2x+18=-20 | | 24x+25=-6y+7 | | 24x+18=-20 | | 2/3y-9=9 | | 2s-15=-1 | | 11-2a=a-7 | | b-5=7b+9 | | 9(z+1)-4z=41 | | 1/3p-2/3p | | 8(x+8)+5=69 | | -(P+5)= | | 1-r+2=2r | | 8x+13y=-54.5 | | -21+3x=39+8x | | -2v-2v=-4v+3 | | b=7b+4 | | F=(9/5)-32 | | 247.8080=r^2 | | b=5m+3 | | (x^2-4x)=0 | | 3/4s=1464. | | (87/2-16)/5= | | x^2-7x=-25 | | -11+12x=12x-11 | | -3y+5x=7 | | 3x+2y-z=-12 | | (A)n=4+(n+1)(-5) | | 5(6+Y)=45 | | X+31=x+19 | | h(t)=-16t^2-20t+120 |